CONFLITO DE PODERES: A AUTONOMIA DO EMPREGADOR E OS DIREITOS FUNDAMENTAIS DO EMPREGADO - Vanzella Correia, Laura; Kauana Lazaretti, Isadora (Seminário de Iniciação Científica e Seminário Integrado de Ensino, Pesquisa e Extensão (SIEPE), 2025)
Pergunta respondida com sucesso This academic study analyzes the complex balance between the powers of employers and the fundamental rights of employees. The research, titled "CONFLITO DE PODERES: A AUTONOMIA DO EMPREGADOR E OS DIREITOS FUNDAMENTAIS DO EMPREGADO" (CONFLICT OF POWERS: THE AUTONOMY OF THE EMPLOYER AND THE FUNDAMENTAL RIGHTS OF THE EMPLOYEE), aims to understand how the 1988 Federal Constitution of Brazil establishes limits on the exercise of employer powers to protect employees' fundamental rights. The study used an analysis of constitutional provisions, specifically Article 5 of the 1988 Federal Constitution, and other labor laws. It also reviewed decisions from Regional Labor Courts, legal documents, and specialized literature on Constitutional Law and Labor Law. The preliminary findings indicate a need for equilibrium between employer prerogatives and the fundamental rights of employees, without compromising the viability of the employment relationship. The research highlights the continuous dialogue between Constitutional Law and Labor Law. The conclusion is that the 1988 Constitution restricts the employer's power to ensure it does not infringe upon the fundamental rights of the worker. This balance requires the employer to act ethically and legally, while the employee fulfills their role responsibly, ultimately creating a labor relationship based on mutual respect, cooperation, and human dignity.